Monte Carlo simulation of air sampling methods for the measurement of radon decay products. (August 2017) - Sima, Octavian; Luca, Aurelian; Sahagia, Maria
Abstract: A stochastic model of the processes involved in the measurement of the activity of the 222 Rn decay products was developed. The distributions of the relevant factors, including air sampling and radionuclide collection, are propagated using Monte Carlo simulation to the final distribution of the measurement results. The uncertainties of the 222 Rn decay products concentrations in the air are realistically evaluated. Highlights: Monte Carlo simulation of active methods for assessment of 222 Rn decay products. Uncertainty evaluation by propagation of distributions, according to JCGM 101. Contribution of stochastic processes (air sampling, filter retention) included. Frequently uncertainties compatible with values computed by traditional approach. In specific cases higher uncertainties than computed with the traditional approach.